2019
DOI: 10.1007/s42452-019-1381-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and addressing uncertainties in empirical vibration attenuation relationship for underground blast by re-sampling

Abstract: For efficient and timely execution of deep excavations, tunnelling or mining activities in rock, controlled blasting often becomes essential. For design of the controlled blasting operation, scaled distance regression analysis of trial blast data, namely, distance, charge weight, and peak particle velocity (PPV), is the regular industrial practice. Due to limited number of input data from trial blasts, and further due to variability of underlying media, multiple uncertainties creep into expressions thus develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Energies 2023, 16, x FOR PEER REVIEW 3 of 16 confidence intervals of GMPE parameters for seismic ground vibrations caused by induced seismicity [23], or blasting works [24]. The purpose of this study is to evaluate one of the most important seismic hazard parameters, i.e., the peak ground acceleration (PGA) estimator, which is based on the bootstrapping statistical procedure on the basis of high-energy mining seismicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2023, 16, x FOR PEER REVIEW 3 of 16 confidence intervals of GMPE parameters for seismic ground vibrations caused by induced seismicity [23], or blasting works [24]. The purpose of this study is to evaluate one of the most important seismic hazard parameters, i.e., the peak ground acceleration (PGA) estimator, which is based on the bootstrapping statistical procedure on the basis of high-energy mining seismicity.…”
Section: Methodsmentioning
confidence: 99%
“…Another application of bootstrapping in seismology is for determining the uncertainty of estimated seismic deformations [18], determining the confidence intervals of the location of historical earthquakes [19], calculating the horizontal component of the seismic slowness vector [20], calculating the b parameter of the Gutenberg-Richter law [21], as well as estimating the uncertainty of the values describing seismic magnitude attenuation function [22]. There are fewer research studies on the use of bootstrapping to calculate the confidence intervals of GMPE parameters for seismic ground vibrations caused by induced seismicity [23], or blasting works [24].…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties in data might be broadly classified as aleatory or epistemic (Tung & Yen, 2005;Coleman & Steele, 2009;Modarres et al, 2010). The aleatory uncertainty is associated with the natural randomness of the process or physical phenomenon and therefore cannot be reduced (Lombardi, 2017;Dauji, 2019). The epistemic uncertainty arises from the deficiencies in information, lack of scientific understanding and inaccuracy in modelling of the physical process and therefore can be reduced with more data and better 171 knowledge of the process (Lombardi, 2017;Dauji, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The aleatory uncertainty is associated with the natural randomness of the process or physical phenomenon and therefore cannot be reduced (Lombardi, 2017;Dauji, 2019). The epistemic uncertainty arises from the deficiencies in information, lack of scientific understanding and inaccuracy in modelling of the physical process and therefore can be reduced with more data and better 171 knowledge of the process (Lombardi, 2017;Dauji, 2019). Rather than classification of uncertainties involved in an analysis, the engineering approach is targeted towards estimation of the uncertainty and incorporating the same into the analysis and safe design of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (Murmu et al, 2018) reported application of Monte Carlo simulation for probabilistic study of blast induced ground vibration using empirical relationship. A method for addressing the uncertainty of the empirical attenuation relationship was presented by Dauji (2019) adopting re-sampling approach.…”
Section: Introductionmentioning
confidence: 99%